2013
DOI: 10.4161/spmg.25385
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase is a regulator of F-actin dynamics

Abstract: During spermatogenesis, spermatogonia (2n, diploid) undergo a series of mitotic divisions as well as differentiation to become spermatocytes, which enter meiosis I to be followed by meiosis II to form round spermatids (1n, haploid), and then differentiate into spermatozoa (1n, haploid) via spermiogenesis. These events take place in the epithelium of the seminiferous tubule, involving extensive junction restructuring at the Sertoli-Sertoli and Sertoli-germ cell interface to allow the transport of developing ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 81 publications
(145 reference statements)
1
28
0
Order By: Relevance
“…In short, the Arp2/3 is a protein complex composed of seven different proteins. Its intrinsic activity is to bind onto the barbed end of an existing actin microfilament, upon activation by N-WASP (neuronal Wiskott-Aldrich syndrome protein), and the N-WASP/Arp2/3 complex rapidly induces branched actin nucleation [5459] (Fig. 1d).…”
Section: Actin-based Cytoskeletonmentioning
confidence: 99%
“…In short, the Arp2/3 is a protein complex composed of seven different proteins. Its intrinsic activity is to bind onto the barbed end of an existing actin microfilament, upon activation by N-WASP (neuronal Wiskott-Aldrich syndrome protein), and the N-WASP/Arp2/3 complex rapidly induces branched actin nucleation [5459] (Fig. 1d).…”
Section: Actin-based Cytoskeletonmentioning
confidence: 99%
“…9,19 The extensive restructuring of basal and apical ES is crucial to spermatogenesis, and recent studies have shown many molecules and signaling pathways participate in ES restructuring. 6,9,11,14,16 However, the precise mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,14 The continuous transport of developing germ cells across the seminiferous epithelium requires the ES to undergo dynamic restructuring in the epithelial cycle. 2,12,15,16 At the early stage of the epithelial cycle, the disassembly and reassembly of the basal ES-BTB is necessary for the transit of preleptotene spermatocytes across the BTB to enter the apical compartment and prepare for meiosis. 2,16,17 After spermatocytes enter the apical compartment, the apical ES replaces the desmosome-like junctions and gap junctions in the Sertoligerm cell interface and persists until the spermatids line up at the luminal edge of the seminiferous tubule.…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis put forward is that biologically active fragments of adhesion-related molecules (γ3-laminin), released or internalized in apical regions in the cell during sperm release, in some way interact with "receptors" at the base of the cell. This then triggers the turnover of basal junction complexes, facilitating spermatocyte translocation [396,399]. The cell biology behind this proposed pathway remains to be elucidated.…”
Section: Regulation Of the Cytoskeletonmentioning
confidence: 95%
“…Many elements of these signaling cascades are present in cytoskeletal-containing features of the Sertoli cell that change during spermatogenesis, most notably the actin-containing ectoplasmic specializations. Key among these elements are the kinases ERK [351], Src [202,350], FAK [396], and ILK [275]. The MAP kinase signaling cascade appears particularly significant in the regulation of ectoplasmic specializations and associated junctions [393,397].…”
Section: Regulation Of the Cytoskeletonmentioning
confidence: 99%